Studi Efek Elektrooptis Pada Minyak Goreng - Widyastuti, Nina; Azam, Much; Firdausi, K. Sofjan (BERKALA FISIKA, 2009)
The aim of this research is to study differences between fresh palm oil and heated palm oil in the external static electric field. The external electric field used at this research was resulted from two parallel plates of 5 × 3 cm, separated by 2.5 cm and applied by high voltage from 0 to 11 kV. Light sources used here were red laser pointer (= 650 nm) and green laser pointer (= 532 nm) to measure change of polarization angle. The heated oil used here was fresh oil that was heated in circa 16 minutes. The results indicate that fresh oil has less average gradient of electro optic polarization (h) than heated oil, both of 650 nm and 532 nm. Theh’s value is measured more significant for = 532 nm than= 650 nm, and moreover can be used to measure the quality of oils based on fresh or polluted oil. Keywords: palm oil, electrooptic, polarization.